The Immune System in Irritable Bowel Syndrome - Barbara, Giovanni (Korean Society of Neurogastroenterology and Motility, 2011)
The potential relevance of systemic and gastrointestinal immune activation in the pathophysiology and symptom generation in the irritable bowel syndrome (IBS) is supported by a number of observations. Infectious gastroenteritis is the strongest risk factor for the development of IBS and increased rates of IBS-like symptoms have been detected in patients with inflammatory bowel disease in remission or in celiac disease patients on a gluten free diet. The number of T cells and mast cells in the small and large intestine of patients with IBS is increased in a large proportion of patients with IBS over healthy controls. Mediators released by immune cells and likely from other non-immune competent cells impact on the function of enteric and sensory afferent nerves as well as on epithelial tight junctions controlling mucosal barrier of recipient animals, isolated human gut tissues or cell culture systems. Antibodies against microbiota antigens (bacterial flagellin), and increased levels of cytokines have been detected systemically in the peripheral blood advocating the existence of abnormal host-microbial interactions and systemic immune responses. Nonetheless, there is wide overlap of data obtained in healthy controls; in addition, the subsets of patients showing immune activation have yet to be clearly identified. Gender, age, geographic differences, genetic predisposition, diet and differences in the intestinal microbiota likely play a role and further research has to be done to clarify their relevance as potential mechanisms in the described immune system dysregulation. Immune activation has stimulated interest for the potential identification of biomarkers useful for clinical and research purposes and the development of novel therapeutic approaches.